Mechanistic Insights of the Interaction of Plant Growth-Promoting Rhizobacteria (PGPR) With Plant Roots Toward Enhancing Plant Productivity by Alleviating Salinity Stress - Bhat, Mujtaba Aamir; Kumar, Vijay; Bhat, Mudasir Ahmad; Wani, Ishfaq Ahmad; Dar, Farhana Latief; Farooq, Iqra; Bhatti, Farha; Koser, Rubina; Rahman, Safikur; Jan, Arif Tasleem (Frontiers in Microbiology, 2020)
Agriculture plays an important role in country’s economy.The sector is challenged by many stresses which led to huge loss inplant productivity worldwide.The ever-increasing population, rapid urbanization with shrinking agricultural lands, dramatic change in the climatic conditions, and extensive use of agrochemicals in agricultural practices that caused environmental disturbances confronts mankind of escalating problems of food security and sustainability in agriculture.Escalating environmental problems and global hunger has led to development adoption of genetic engineering and other conventional plant breeding approaches in developing stress tolerant varieties of crops. However, these approaches have drawn flaws in their adoption as the process of generating tolerant variety takes months to years in bringing the technology from lab to field.Under such scenario, sustainable and climate smart agricultural practices that avails bacterial usage opens the avenues in fulfilling the demand of food for incessant increase in the global population.Ensuing stability on economic fronts, bacteria minimizes plant salt uptake by trapping ions in their exopolysaccharide matrix, besides have a check on the expression of Na+/H+ and high affinity potassium transporters. Herein, we describe the information on salinity stress and their effect on plant health, strategies adopted by plant growth promoting rhizobacteria (PGPR) in helping plants to overcome the salinity stress and in mitigating loss in overall plant productivity. It is believed that acquisition of the advanced knowledge of plant beneficial PGPR will help in devising strategies forsustainable, environment friendly and climatic smart agricultural technologies for adoption in agriculture to overcome constrained environmental conditions.